Index measured gender equitable knowledge for CSAPs adoption assuring food & nutrition security under climatic risks: Bihar, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The results have created realization of education for CSAPs adoption among community and requires focus. With the observed benefits of ensured food&nutrition security with higher yield and income, the portfolio of CSAPs is targeted by sub-national government& other dissemination agencies using the business models developed